All Days 2012
DOI: 10.2118/152112-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Development Study: Channel Fracturing Increases Gas Production and Improves Polymer Recovery in Burgos Basin, Mexico North

Abstract: The channel fracturing technique combines fracture modeling, materials and pumping methods to generate a network of highly conductive channels within the proppant pack. These channels aim at expediting the delivery of hydrocarbons from the reservoir to the wellbore (Gillard et al., 2010). This paper provides a comprehensive summary of the implementation of this novel technique in the Burgos basin, Mexico North. The Eocene Yegua formation in the Palmito field near Reynosa, Mexico was selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Sadykov et al, 2012 For example, in the Loma La Lata field in Argentina (Gillard et al, 2010) fracture conductivities were found to be 1.5 to 2.5 orders of magnitude higher than the theoretical conventional fractures. In their study for the Burgos basin, Valenzuela et al (2012) mention that the observed increases in well productivity with the use of the channel fracturing technique were obtained with a smaller proppant mesh size (20/40 mesh) than that used in the conventional stimulation operations (16/30 mesh). This result is counterintuitive to conventional fracturing methods, which customarily rely on larger proppant mesh sizes to increase the average proppant pore dimensions, and therefore fracture conductivity and well production.…”
Section: Fracture Conductivitymentioning
confidence: 99%
“…Sadykov et al, 2012 For example, in the Loma La Lata field in Argentina (Gillard et al, 2010) fracture conductivities were found to be 1.5 to 2.5 orders of magnitude higher than the theoretical conventional fractures. In their study for the Burgos basin, Valenzuela et al (2012) mention that the observed increases in well productivity with the use of the channel fracturing technique were obtained with a smaller proppant mesh size (20/40 mesh) than that used in the conventional stimulation operations (16/30 mesh). This result is counterintuitive to conventional fracturing methods, which customarily rely on larger proppant mesh sizes to increase the average proppant pore dimensions, and therefore fracture conductivity and well production.…”
Section: Fracture Conductivitymentioning
confidence: 99%
“…In an application of channel fracturing in the desert of western Egypt, an 89% increase in initial production was observed (Gawad et al 2013). A production increase of 29% was reported after applying channel-fracturing stimulation in Taylakovskoe Field in Siberia (Valiullin et al 2015). Li et al (2015a) reported stimulation results for channel fracturing in tight oil and gas reservoirs in Ordos Basin, China; the production of oil wells increased by 1.4 times and gas-well production increased by three to five times.…”
Section: Introductionmentioning
confidence: 98%
“…This technology provides high fracture conductivity (ie, 2‐3 orders larger than conventionally propped fractures) and low cost due to reduced material usage, thereby decreasing the flow resistance of hydrocarbons and increasing production 14 . According to statistics, by applying channel fracturing technology, the improvement of hydrocarbon production ranges from 19% to 98% 15‐19 …”
Section: Introductionmentioning
confidence: 99%
“…14 According to statistics, by applying channel fracturing technology, the improvement of hydrocarbon production ranges from 19% to 98%. [15][16][17][18][19] Multiple studies have been published on the conductivity of channel fractures; for example, Medvedev et al 20 concluded that the discontinuous distribution of proppant packs largely enhances the channel fracture conductivity and determines the optimal channel width. Additionally, Zheng et al 21 found that with the increase in the distribution density of proppant packs, the channel fracture conductivity increased at the beginning and then decreased rapidly, while Xu et al 22 proposed that fracture width, propped area, and proppant embedment were the key factors affecting channel fracture conductivity.…”
mentioning
confidence: 99%